Investigation of vortex-induced vibration of a cable-stayed bridge without backstays based on wind tunnel tests. (1st January 2022) - Wu, Yanru; Wu, Xiaohong; Li, Junxin; Xin, Haohui; Sun, Qing; Wang, Jiantao
Highlights: This paper conducted the full-aeroelastic model test and segmental model test. The effect of different factors on the vortex-induced responses are investigated. This paper identifies the vortex-induced resonance based on response power spectrum. An aerodynamic configuration is obtained to improve vortex-induced vibration. Abstract: Cable-stayed bridges without backstays located in the abrupt valley are sensitive to wind-induced structural vibrations. The understanding of vortex-induced vibration for specific aerodynamic configuration with glass deck is of great importance for structure design. This paper thus aims to investigate the vortex-induced vibration of a cable-stayed bridges without backstays through the segmental model test and scaled full-aeroelastic model wind tunnel test. The results indicate that the bridge presents the vertical vortex-induced vibrations at the low wind speed whereas the maximum wind velocity causing the torsional vortex-induced vibrations increases to 41 m/s, which is much larger than that of the traditional bridge. The vertical and torsional vortex-induced vibrations in the smooth flow are observed at the positive wind angle of attack, owing to the responses for the bridge deck present a sharp single-frequency amplitude when the frequency of vortex-shedding is close to the flexural vibration frequency. The turbulence can effectively suppress the vortex-induced vibrations and only some small peaks are visible in the turbulent flow. The vortex-induced response of the bridge deck is significantly alleviated with increasing of damping ratio. Finally, the vortex-induced vibrations in the uniform flow disappear and the wind-induced responses are impaired with the ventilated railing in place of the airtight railing because the flow can go through the railing. It can provide a designing basis for engineering reference of cable-stayed bridges without backstays.